Development of a Database Geographic Information System (GIS) of The Soil Profile At Fringe Villa Forest City, Tanjung Kupang, Johor - Mohd Zainuaddin, Maisara Rezky Janna; Abu Talib, Zaihasra (Recent Trends in Civil Engineering and Built Environment, 2021)
In this era of information technology, all data management and information are done through online. The purpose of this study is to obtain a Geographic Information System (GIS) database with information on the soil profile in Fringe Villa Forest City, Tanjung Kupang, Johor to provide the information needed by users for learning, development purposes, and many more. Therefore, a database is built and stored in QGIS software so that information management systems were more effective. The methodology of the study begins with the data collection, selection software, design and development database, and data analysis. The data obtained are from the Department of Mineral and Geoscience (JMG) Johor for soil investigation reports included plan which is the hard copy and was developed using QGIS software. In this project, Microsoft Excel software was used to store attribute data in a tabular form. QGIS is a GIS software that was used to digitize the study area, obtain the value of coordinate and create a database that enables the mapping of classification of soil profile within a Fringe Villa Forest City, Tanjung Kupang, Johor. The analysis result shows the use of GIS can assist in the development and reference of soil properties in the Fringe Villa Forest City, Tanjung Kupang, Johor more systematically while saving time and energy.